Peer Assisted Learning Strategies (PALS) for Enhancing the Reading Skills of Students with Disabilities at Inclusive Schools - Dr. V. Mrunalini, Dr. S. Revathi, N. Ilakkiya (Journal of Neonatal Surgery, 2025)
Background: Students with disabilities in inclusive schools often face significant challenges in developing effective reading skills. Peer Assisted Learning Strategies (PALS) have been proposed as an effective approach to improve reading outcomes through structured peer tutoring techniques. This study evaluates the impact of PALS on reading skills among students with disabilities. Objectives: To assess the effectiveness of Peer Assisted Learning Strategies (PALS) in enhancing reading achievement among students with disabilities in inclusive classrooms. Methods: A total of 198 students from Classes I to V were selected using purposive sampling. The intervention included four key PALS techniques: partner reading, paragraph shrinking, quiz activities, and project-based peer collaboration. A pre-test and post-test design was employed. Reading achievement served as the dependent variable, while class levels served as the independent variable. Statistical analysis was conducted, with reading scores compared pre- and post-intervention using t-tests. Results: The post-test results indicated a marked improvement in reading achievement, with a standard deviation of 3.58 and a t-value of 39.11, confirming a statistically significant enhancement (p < 0.05). The PALS intervention demonstrated notable success across all class levels. Conclusion: Peer Assisted Learning Strategies significantly improved the reading skills of students with disabilities in inclusive settings. PALS is recommended as an effective instructional strategy for promoting literacy development in inclusive education environments.